Gender differences among criminal justice-involved persons living with HIV interested in extended-release naltrexone treatment. Issue 4 (2nd October 2021) - Biondi, Breanne E.; Frank, Cynthia A.; Forray, Ariadna; Springer, Sandra A.
Abstract: Background: Previous research has shown gender differences with respect to entry into medication treatment of substance use disorders (SUDs), yet few have examined gender differences among participants consented to be treated with extended-release naltrexone (XR-NTX). Understanding gender differences is critical to developing interventions to overcome barriers to initiation of and retention on medication treatment for SUDs. Methods : Data from two double-blind placebo-controlled trials of XR-NTX among persons with HIV and alcohol or opioid use disorders leaving the criminal justice system (CJS) were analyzed for gender differences among clinical characteristics, mental health, drug use severity, and other domains. The study that recruited persons with alcohol use disorder (AUD) was conducted from September 2010–February 2016 at two sites in Connecticut (CT), and the opioid use disorder (OUD) study was conducted from September 2010–March 2016 at three sites in CT and one site in Massachusetts. Results : Baseline data were analyzed from 193 participants consented to be randomized to XR-NTX or placebo; 40 women and 153 men. Women were younger, had worse mental health severity, and were more likely to be diagnosed with cocaine use disorder. There were no statistical differences between men and women in the prescription of antiretroviral therapy (ART) or ART adherence. Conclusions : Women had greater mental health severity and a higher prevalence of cocaine use as compared to men, both of which are known to be barriers to engagement and retention on medication treatment for alcohol and opioid use disorders. For women with CJS involvement and living with HIV and SUDs, understanding factors that may affect initiation and retention on medication treatment of SUDs are necessary to improve treatment outcomes in women.